Elastic Bunch Graph Matching Based Face Recognition Under Varying Lighting, Pose, and Expression Conditions - Farooq Ahmad Bhat; M. Arif Wani (Institute of Advanced Engineering and Science, 2014)
In this paper performance of elastic bunch graph matching (EBGM) for face recognition under variation in facial expression, variation in lighting condition and variation in poses are given. In this approach faces are represented by labelled graphs. Experimental results of EBGM on ORL, Yale B and FERET datasets are provided. Strong and weak features of EBGM algorithm are discussed.